Body image perception in Mexican university athletes VS non-athletles - Peinado Pérez, Jesús Enrique; Rodríguez Villalobos, Judith Margarita; Aguirre Chávez, Juan Francisco; Tristán Rodríguez, José Leandro; Castillo Fernández, Isabel María (Science Publishing Group, 2014)
The objective of this study consisted in determining the differences and similarities among Mexican University students who practice a sport on a regular basis with those who do not do, concerning their body image perception to their actual, ideal, social and body size dissatisfaction. A total sample of 304 male University students, aged 18-29 years participated in this study; 146 of them practice a sport and participate regularly in a tournament or competition. A quantitative approach with a descriptive and transversal survey design was used. All the participants completed the Contour Drawing Rating Scale adapted and computerized by [1]. The results of the one-way multivariate analysis of variance, followed by the one-way univariate analyses of variance, show that university students who don’t participate in a regular sport are the ones who show thicker models for their present, ideal and social figure, in addition to demonstrating higher body size dissatisfaction. Further research should reply these findings in larger samples.